Pengaruh Keberadaan TPA terhadap Kualitas Air Bersih Diwilayah Pemukiman Warga Sekitar: Studi Literatur - Ahmad Walid; Raden Gamal Tamrin Kusumah; Erik Perdana Putra; Wira Herlina; Puji Suciarti (Universitas Batanghari Jambi, 2020)
The influence of the presence of landfill in the presence of pollution can occur in the air as a result of waste decomposition, can also pollute water and soil caused by leachate seepage. Piles of garbage can cause physical and chemical environmental conditions to be incompatible with normal conditions. This research method uses a study method literature by collecting data by looking for relevant references and facts to get an argumentative description of the effect of the landfill, the literature is filtered and connected to get conclusions to understand the impact of the presence of landfill on the quality of clean water in the surrounding environment. Results obtained and concluded cities which are stockpiled at the final processing site (TPA), have the potential to cause environmental pollution, both surface and ground water pollution and soil pollution due to leachate.